The population of phosphate solubilizing bacteria (PSB) from Cikaniki, Botol Mountain, and Ciptarasa Area, and the ability of PSB to solubilize insoluble P in solid pikovskaya medium - SRI WIDAWATI; SULIASIH SULIASIH (Society for Indonesian Biodiversity, 2006)
Phosphate solubilizing bacteria (PSB) were collected from plant rhizosphere at Cikaniki (1100 m asl.), soil at Botol Mountain (1000, 1500, and 1800 m asl.), and Ciptarasa (600, 1000, and 1500 m asl.), area at Gunung Halimun National Park (GHNP). The soil ware collected randomly from 3 areas and taken from 0-15 cm depth in the plants rhizosphere at Cikaniki and forest floor soil in Gunung Botol and Ciptarasa. The result showed that the difference of elevation area, soil pH, forest vegetation, and microbial habitat (rhizosphere and forest floor) were not the inhabitation factors of the biodiversity of PSB and their ability to solubilize insoluble phosphate, but the inhabitation factors on the growth of the PSB population. The highest population of PSB at GHNP was founded in the plant rhizosphere of Altingia exelsa Norona and Schima wallichii (Dc.) Korth (107sel/g soil) at Cikaniki and in the forest floor soil (108sel/g soil) at Botol Mountain (1000 m asl.). Pseudomonas sp., Bacillus sp., Bacillus megaterium, and Chromobacterium sp. dominated Cikaniki, Botol Mountain and Ciptarasa area. Those isolates could solubilize insoluble phosphate on solid Pikovskaya medium with the range of diameter is 1.5-2.5 cm. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: phosphate solubilizing bacteria (PSB), Cikaniki, Gunung Botol, and Ciptarasa area.